1994
DOI: 10.1177/026921559400800311
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training in brain-injured patients

Abstract: A pilot study was performed to assess the value of aerobic training as part of the rehabilitation programme for patients with a single incident brain injury requiring admission to an inpatient neurological rehabilitation unit. The cohort consisted of six patients with a combination of impairments including weakness, spasticity, taxia and cognitive problems. Each patient performed an exercise test at the beginning and end of the study to assess changes in aerobic fitness and performance. The aerobic training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…A detailed analysis was performed of sub-maximal responses to exercise on a minute-by-minute basis. Decreases in sub-maximal heart rates of patients with ABI have been shown by other investigators after a training intervention [13,15,17]. A lower heart rate at a given sub-maximal workload suggests an increase in stroke volume and an improvement in the pumping ability of the left ventricle.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A detailed analysis was performed of sub-maximal responses to exercise on a minute-by-minute basis. Decreases in sub-maximal heart rates of patients with ABI have been shown by other investigators after a training intervention [13,15,17]. A lower heart rate at a given sub-maximal workload suggests an increase in stroke volume and an improvement in the pumping ability of the left ventricle.…”
Section: Discussionmentioning
confidence: 61%
“…All but three of the subjects increased their total ambulation time, which equates to an increase in workload. Others have reported an increase in total exercise time on a cycle ergometer [12,15,16]. In each of these studies, subjects were both tested and trained on a stationary bicycle and each found an increase in exercise tolerance and exercise capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Second, data were not collected to socially validate the effects of increased exercise engagement for the participants. Despite the absence of formal measures of social validity, participants' reported that they enjoyed exercising and prior studies have found that increased exercise was highly valued by participants and their families (e.g., DeLuca & Holborn, 1992;Wolman et al, 1994). Moreover, as each of the participants had experienced weight-gain as a side-effect of psychotropic medication, the establishment of a consistent workout routine may have helped the participants counteract such effects.…”
Section: Discussionmentioning
confidence: 99%
“…The results contribute to the literature by showing that a relatively simple intervention can be used to increase exercise participation by individuals with ABI. Results from prior studies suggest that increased exercise may increase independence and quality of life for individuals with ABI (e.g., Driver et al, 2006;Gordon et al, 1998;Jankowski & Sullivan, 1999;Sullivan et al, 1990;Thompson & Born, 1999;Wolman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation